Why do you lead the way you do? - Peters, John (Henry Stewart Talks, 2019)
Developing leaders, Character, Capabilities, Knowledge, Uncertainty, Leadership Effectiveness & Agility Profile (LEAP), Dynamic core, Reflective practice, Unilever’s sustainable living plan, Legacy, Leadership philosophy, Countdown thinking